The Correlation Between Language Learning Strategies and Students’ Thinking Style at 1ST Junior High School Students of MTs. Mawaridussalam Batang Kuis in The Academic Year of 2021/2022 - Dewi Kartika Rani; Yani Lubis; Achmad Ramadhan (BRIGHT VISION, 2026)
The objectives of this research were to determine (1) whether there is any significant correlation between language learning strategies and students’ thinking style (2) whether language learning strategies significantly influence students’ thinking style at 1st Junior High School students of MTS Mawaridussalam Batang Kuis in the academic year of 2021/2022. This study's population included 178 students.The researcher took VII-5 class as sample of this study were chosen for this study using the simple random sampling method. A correlational method was used in this study.Questionnaire were used to collect data. In this study, there are two kinds of questionnaires. There are 50 questions about language learning strategies and 65 questions about students' thinking styles. SPSS 22 was used to calculate the data which was analyzed using the Pearson Product Moment Correlation coefficient and Simple Linear Regression.The findings of this study show a correlation coefficient is 0.621, with the sig. value 0.000 < 0.05, indicating that there is a significant correlation between two variables. Moreover, the coefficient of determination (R2) is 0.386. It indicates that the language learning strategies variables affect 38.6 % on students' thinking styles. Based on the findings, it is reasonable to conclude that there was positive correlation between language learning strategies and students thinking styles.